Caracterización morfológica de almidones de los géneros Triticum y Hordeum en la Península Ibérica (2012)
ABSTRACT: Starch grains are increasingly used in archaeobotanical studies as markers of diet, plant domestication, tool use and site organization in archaeological research, because their morphology and features provide a means to identify the plant that produced them. In this paper we characterize morphometrically the starch grains of five species of the genus Triticum and three varieties of Hordeum vulgare. In addition there is an assessment of the studies of starch grains made in the Prehistory of the Iberian Peninsula, indicating the achievements, the weaknesses and future directions to promote this type of bioarchaeological analysis; especially, there is a need to rely on wide reference collections, as well as apply statistical analyses and carry out experimental studies to control the processes of alteration of the starch grains.